The Role AI in Securing Immigration Data: A Descriptive Study of Digital-Era Protection Policies - Nurul Maharani Piranti; Mila Rosmaya; Muhammad Fahrury Romdendine; Cakra Trinata; Okky Pratama Martadireja (International Journal of Multidisciplinary Approach Research and Science, 2026)
The digital transformation of immigration systems has introduced significant challenges to personal data protection, particularly from escalating cyber threats. Critical digital infrastructure, including SIMKIM, e-Visa, and autogate, handles sensitive data whose breach could severely compromise national security and individual privacy. This qualitative descriptive study analyzes Indonesia's immigration data protection policies and evaluates the potential of Artificial Intelligence (AI) as a strategic tool for cyber threat mitigation. Our findings, based on a comprehensive literature review, indicate that current legal frameworks are largely normative, lacking specific technical provisions for data protection within this sector. In contrast, AI technology shows immense promise for detecting system anomalies, enhancing audit capabilities, and preventing data breaches. Consequently, this study recommends implementing specific sectoral technical regulations, investing in digital human resource capacity, and deploying AI-driven systems to secure immigration data, thereby laying a foundation for a risk-based, adaptive digital security governance framework.